Златната книга на константиновиот ред на свети Ѓорѓи и грбот на охридскиот архиепископ Јоасаф II - The Golden Book of the Constantinian order of St. George and the Coat of Arms of the Archbishop of Ohrid Joasaph II - Jonovski, Jovan (Македонски хералд - Macedonian Herald, 2023)
The Holy Military Constantinian Order of Saint George was established in 1545 as a fantasy order claiming the non-existent Byzantine tradition of Orders of Chivalry. But latter was accepted by Papacy as a legitime order. After the Grand Master title was sold to Francesco Farnese, Duke of Parma in 1697, several pretenders in the Holy Roman Empire were sanctioned by the emperor. Prince Radu Cantacuzino, eldest son of Ștefan, Prince of Wallachia (1714–1716), was the Grand Master of the Constantine Order of Saint George who created the Golden Book of the order in 1717. As the Supreme Grand Prior of the Order, the arms of Joasaph IV, Archbishop of the Justiniana Prima and of all Albania, as well as of Macedonia, Thessaly, and Illyricum is depicted. He is most probably the head of the orthodox Archbishopric of Ohrid, Joasaph II (1719-1745). His coat of arms is registered in the book in 1718, a year before Joasaph was elected to the position. The arms are drawn in Catholic style, consistent of 6 fields that might be interpreted as dominion arms, of the land/provinces under his jurisdiction. We try to interpret the lands based on the Zhefarovic Stemmatographia. A remarkably similar coat of arms, this time attributed to an unnamed Archbishop of Ohrid, was published in Russian Grboved in 1903. The article gives the explanation of the quarters which do not fit in with the arms of the lands mentioned.